Effects of age on physical match performance in professional soccer players - Rey, E.; Costa, P. B.; Corredoira, F. J.; Sal de Rellán Guerra, A. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to evaluate the effects of age using a large-scale analysis of match physical performance in professional soccer players. A total of 10,739 individual match observations were undertaken on outfield players competing in the first and second divisions of the Spanish soccer professional leagues during the 2017-2018 season, using a computerized tracking system (TRACAB, Chyronhego, New York, NY). The players were classified into five positions and into 5 age groups (<20 years, 20-24.9 years, 25-29.9 years, 30-34.9 years, and =35 years). The results showed that (a) professional soccer players aged =30 years exhibit a significant decrease (p < 0.01) in the total distance covered, medium-speed running distance, high-speed running (HSR) distance, very HSR (VHSR) distance, sprint distance, and maximum running speed compared with younger players (<30 years); (b) professional soccer players aged =35 years exhibit a significant decrease (p < 0.01) in the number of HSR, number of VHSR, and number of sprints compared with younger players (<35 years); and (c) all playing positions reduced their physical performance; however, external midfielders were less affected by age effects. In conclusion, this study demonstrates players' physical match performance reduces with increasing age. Such findings may help coaches and managers to better understand the effects of age on match-related physical performance and may have the potential to assist in decisions regarding recruitment and player list management within professional soccer clubs.